Effect of Mg incorporation on the properties of PCL/Mg composites for potential tissue engineering applications - Nuthana Kalva, Sumama; Ali, Fawad; Subhadra Keyan, Kripa; Khan, Omar M.; Pasha, Mujaheed; Velasquez, Carlos A.; Koç, Muammer (Frontiers in Materials, 2024)
Polycaprolactone (PCL) is a biocompatible polymer readily moldable into various shapes and designs. However, its low mechanical strength and slow biodegradation restrict its use in tissue engineering. Magnesium (Mg), a biocompatible metal with excellent osteoconductivity and biodegradability, is a promising choice for tissue engineering applications. This study investigates the influence of Mg incorporation on the properties of PCL/Mg composites, aiming to evaluate their suitability for 3D-printable (3DP) tissue engineering applications. We synthesized a series of PCL/Mg composites with varying Mg concentrations and characterized their mechanical, thermal, and degradation properties. According to microscopic analysis of the composite films, the Mg particles are dispersed consistently throughout all the compositions. The findings demonstrated that adding Mg influenced PCL’s mechanical and thermal properties. The mechanical test results showed that the tensile strength of 15% Mg composite filaments improved by around 10% compared to the neat PCL filaments. However, the elastic modulus decreased by around 50% for the same composition. The thermal study revealed a significant reduction in the degradation temperature from above 400°C for pure PCL to around 300°C for PCL/Mg composite having 15% Mg. Additionally, the weight loss during in vitro degradation showed that the presence of Mg had significantly increased the degradation rate of composite samples. Also, Mg incorporation influences cell adhesion, with better attachment observed for 10% Mg 3DP samples. Overall, PCL/Mg composites offer a solution to overcome the limitation of low thermo-mechanical properties typically associated with the PCL.